(3EjVGM cTa GdOSGFS aj efY JQeje GdcfGFSs - (3Ydj Hf YHO GdcGaj Hf Ydj Hf JeGe GdSHcj GdCfUGQj GdNRQLj, CHh GdMSf, Jbqj GdOjf,J (B756 (3g` s
(3ChdgG (B:s
(3CeG HYO SFd Yf JQeje GdcfGFS Ch EYGOg GdcfjSI GdeVeMdI aCQOJ Cf CfXQ eG ajgG ef GdGOdI hCRjd eG MUd ajgG ef GdYdI hPdc NWGHkG HELeGY GdeSdejf aEf HfGA GdcfjSI MQGe HGdGLeGY hcPG JQejegG s
(3BNQgG (B:s
(3hefYhG Cf jMOKhG HYOeG UGQ eUQkG hEPG cGf gPG cdGege ai GdGMOGK aGdJQeje CSgd hdcf GdMb GdefY ef GdJQeje hGddg JYGdi GYde s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJHJ Yf fSNI GdeDda s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds